2017
DOI: 10.21010/ajtcam.v14i2.35
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Rheum Palmatum L. In the Treatment of Acute Respiratory Distress Syndrome: A Meta-Analysis of Randomized, Controlled Trials

Abstract: Background: Chinese medicine theory shows that "lung being connected with large intestine", and the modern western

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It has been used for a variety of conditions, such as constipation, chronic renal failure, and upper gastrointestinal bleeding. It has antimicrobial and antioxidative effects [17,18] e toxicity includes hepatotoxicity and nephrotoxicity. No adverse reactions were observed in mice with a dose of 400 mg/kg [19] Carthamus tinctorius L., safflower, Hong Hua, 3-10 g e flowers of safflower contain kaempferol and hydroxysafflor yellow [20] It reduces immune inflammatory response [14].…”
Section: Size Of Neoplasmmentioning
confidence: 99%
“…It has been used for a variety of conditions, such as constipation, chronic renal failure, and upper gastrointestinal bleeding. It has antimicrobial and antioxidative effects [17,18] e toxicity includes hepatotoxicity and nephrotoxicity. No adverse reactions were observed in mice with a dose of 400 mg/kg [19] Carthamus tinctorius L., safflower, Hong Hua, 3-10 g e flowers of safflower contain kaempferol and hydroxysafflor yellow [20] It reduces immune inflammatory response [14].…”
Section: Size Of Neoplasmmentioning
confidence: 99%
“…Traditional Chinese medicine Rheum palmatum L. (Rhubarb) has been widely used for treating inflammatory diseases for thousands of years in China. Previous research reported that Rheum palmatum L. combined with routine comprehensive treatment remarkedly decreased the mortality of patients with acute respiratory distress syndrome by reducing the mechanical ventilation time, ameliorating the arterial blood gas and the cytokine levels ( Yang et al, 2017 ). Emodin, a main effective ingredient of Rhizoma palmatum L., has been reported to protect against ALI animal models, which is associated with the downregulation of the pre-B-cell colony-enhancing factor, upregulation of aquaporin 1 and aquaporin 2, and inhibition of NF-κB ( Xiao et al, 2014 ; Xu et al, 2016 ; Cui et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous report linking naturally occurring starch with a slow absorption rate suggested that many individuals are only partially capable of digesting plant starch, and high starch contents in herbal decoctions may lead to adverse drug reactions such as bloating, indigestion, and acid reflux. 9 FDY2004 is a processed formulation derived from Daehwangmokdanpi-tang (named Dahuangmudani-tang in China), which comprises Rheum palmatum, 10 Paeonia suffruticosa, 11,12 and Prunus davidiana 13 ; it is known to be effective against pancreatitis 14,15 and to have anti-inflammatory and antiproliferative effects in cancer cells through downregulation of matrix metallopeptidase 2 (a cancer cell metastasis factor), 16 interleukin -1β, and tumor necrosis factor-α (an inflammatory gene). 17 Therefore, it is expected to have an antiproliferative effect in other cancer cells.…”
mentioning
confidence: 99%